EFFECT OF OOCYTE AGE AND ACTIVATION AGENTS ON IN VITRO DEVELOPMENT OF MOUSE PARTHENOGENETIC EMBRYOS - T.M. Hine1; W.M. Nalley; K. Uly; A.E.Manu; J. Ly; A. Marawali; P. Kune (Journal of Animal and Plant Sciences, 2021)
The present study was conducted to explore the effect of oocyte age and activation agents on initiation and development of mouse parthenogenetic embryos. A total of 943 mouse oocytes were divided into 9 treatments based on a completely randomized design with 3 x 3 factorial patterns; with the first factor was oocyte ages: 14-, 17- and 20-hr-old (were calculated based on the time of oocytes collection after the administration of hCG) and the second factor was activation agents (ethanol, calcium ionophore A23187, strontium chloride). The oocytes were exposed to 5 µg/ml cytochalasin B and then cultured in potassium simplex optimization medium at 37oC under 5% CO2 up to 5 days. The results showed that the highest number of good quality oocytes was obtained by 14-hr after the administration of hCG. The level of activation and 2 pronuclei (2 PN) increased significantly in 17- and 20-hr-old oocytes (P≤0.05). The highest rate of embryonic development and blastocyst cell counts produced by 17-hr-old oocytes activated by strontium chloride (P ≤0.05). It is concluded that initiation and in vitro development of mouse parthenogenetic embryos are affected by the age of oocytes and activation agents, with strontium chloride is the best activation agent especially in 17-hr-old oocytes.
Keywords: activation agent; oocytes age; parthenogenetic embryos; mouse